2020
DOI: 10.1159/000505486
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Toxicity in Cancer Patients Treated with Tyrosine Kinase Inhibitors: A Real-World Single-Center Experience

Abstract: Background: Target therapy can cause various cardiovascular complications. The aim of this study was to evaluate the burden of cardiovascular complications related to treatment with anti-BCR-ABL tyrosine kinase inhibitors (TKIs) and to determine if there are differences between the latest-and firstgeneration TKIs. Methods: A retrospective observational study was carried out on 55 patients (39 men, 16 women; mean age ± SD: 58 ± 11 years) treated with TKIs targeting Bcr-Abl for a median period of 3.5 years. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Arterial stiffness may be influenced by anthracyclines with different mechanisms. Oxidative stress with the release of free oxygen radicals (induced by anthracyclines; Di Lisi et al, 2017;Novo et al, 2020) would increase arterial stiffness through structural changes within the vascular matrix, interfering with the endothelial regulation of vascular smooth muscle cell tone.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial stiffness may be influenced by anthracyclines with different mechanisms. Oxidative stress with the release of free oxygen radicals (induced by anthracyclines; Di Lisi et al, 2017;Novo et al, 2020) would increase arterial stiffness through structural changes within the vascular matrix, interfering with the endothelial regulation of vascular smooth muscle cell tone.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with first-generation imatinib highlights the increased risk of hypertension events in patients treated with NGTKI, especially with nilotinib and ponatinib. Recently, a real-life monocentric experience showed an increased incidence of cardiovascular events in patients treated with nilotinib and dasatinib compared to the imatinib group, in particular with an increased incidence of hypertension of 7 and 4%, respectively ( Novo et al, 2020 ). Exposure to more than two lines of treatment can be another important element of increased risk in hypertension events.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper published by Novo et al, it was suggested that the latest generation of TKIs used in the treatment of CML (nilotinib, dasatinib, and ponatinib) may increase the incidence of CV events; they also observed pleural effusions [ 38 ]. In our study, 8/43 patients (18.60%) treated with nilotinib and dasatinib developed pericardial effusion, and two of them presented moderate pleural effusion.…”
Section: Discussionmentioning
confidence: 99%
“…Levato et al observed a 14.8% incidence of progressive LEAD and other vascular events during nilotinib therapy [ 39 ]. The probability of remaining free of progressive LEAD is higher in patients treated with imatinib compared to those with nilotinib regimens [ 38 ].…”
Section: Discussionmentioning
confidence: 99%